2017
DOI: 10.1159/000480124
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries and Developmental Defects of Enamel in the Primary Dentition of Preterm Infants: Case-Control Observational Study

Abstract: Aim: Assessment of dental health in the primary dentition of preterm infants (PTI) including investigation of mother- and infant-related risk factors in a case-control study design. Material and Methods: One hundred twenty-eight infants aged 3-4 years were included. Sixty-four PTI (27 males) were randomly selected from the preterm registry of the Jena University Hospital. As a control group served 64 full-term infants (FTI) recruited from the Department of Paediatric Dentistry, matched for age and sex. Dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 58 publications
(102 reference statements)
4
66
0
6
Order By: Relevance
“…This study observed significant differences in DDE prevalence and EDS between boys and girls. A similar result was reported in children from Beijing, China; Manyara, Tanzania; and Nigera but not among German children or children from Cook Island . Despite the lack of clear explanations for these controversial findings, scientists have demonstrated that the ameloblasts are extremely sensitive to serum calcium fluctuations over even short periods of time .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study observed significant differences in DDE prevalence and EDS between boys and girls. A similar result was reported in children from Beijing, China; Manyara, Tanzania; and Nigera but not among German children or children from Cook Island . Despite the lack of clear explanations for these controversial findings, scientists have demonstrated that the ameloblasts are extremely sensitive to serum calcium fluctuations over even short periods of time .…”
Section: Discussionsupporting
confidence: 83%
“…Subsequent evidence has shown that nutritional deficiency, particularly maternal prenatal vitamin D deficiency, influenced DDE in primary dentition and caries development . Other maternal factors, including pregnancy stress, poor maternal nutrition, exposure to infections and parenting behaviours, have also been reported to influence primary tooth development and the caries statuses of children . Although this cross‐sectional study was not enable to determine those associations, the concordant results of the DDE difference between the boys and girls in the two studies suggest a plausible biological link between gender susceptibility to DDE among Chinese preschool children.…”
Section: Discussionmentioning
confidence: 80%
“…Inconsistency was a serious problem. The majority of studies (28 out of 36) found no association between dental caries and premature birth, but four studies found that caries experience was more common among preterm children and another four studies found that caries experience was more common among full‐term children . Moreover, seven out of 50 studies found that caries experience was more common among children with LBW and only one study found that caries experience was more common among children with NBW .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have addressed the association between dental caries and preterm birth and/or LBW, but the findings remain unclear due to methodological differences and conflicting conclusions . Therefore, the aim of the present systematic review and meta‐analysis was to evaluate the prevalence of dental caries (outcome) in preschool children (patients) born preterm and/or with a LBW (exposure) compared to children born full term and/or with a normal birth weight (NBW) (comparison).…”
Section: Introductionmentioning
confidence: 99%
“…However predisposition to dental caries in premature children is somewhat controversial, because of the scarcity of studies and necessity to evaluate other primary and secondary risk factors as well as socio-economic consequences [8,9]. One study by Schüler et al found an association of dental caries with low socio-economic status [10].…”
Section: Discussionmentioning
confidence: 99%